Family medicine research in Kazakhstan: challenges, needs and support - Zhamaliyeva, Lazzat; Donayeva, Ainur; Abenova, Nurgul; Dilmagambetova, Gaukhar; Koshmaganbetova, Gulbakit; Pavlič, Danica Rotar; Begalina, Dana; Yessengalieva, Inkara; Ismailova, Irina; Bolsyn, Assel (Bangladesh Journal of Medical Science, 2024)
Family medicine (FM), a relatively new speciality, has actively addressed the issue of research, despite the fact that, until recently, the majority of family doctors defined themselves in terms antithetical to research. Initial attempts in developing countries have typically concentrated on clinical care and teaching, with engagement in research being less common. The aim of the study is to investigate family the FM specialists’ perspectives on research engagement in Kazakhstan employing a mixed-methods research design with the collection of both quantitative and qualitative data. We surveyed 83 FM specialists to better understand the needs and barriers faced by this community in conducting research. Semi-structured interviews were conducted to obtain an in-depth picture of the issues. Understanding these issues is central to developing informed policies for promoting FM specialists’ research engagement, as well as taking steps to build their research capacity. The study resulted in important findings in understanding the specialists’ challenges in conducting research, and the needs and support provided to researchers in FM in Kazakhstan. The research barriers are a lack of time to conduct research, difficulty in publishing research, and a lack of cooperation between peers and research mentoring from experienced professionals. Specialists’ needs include specialized training programs and internships, a team of like-minded people and research partnerships, and access to patient databases and archived data. The specifically targeted policies should be undertaken to facilitate the specialists’ research careers by promoting research engagement, fostering research capacity, and recognizing FM as a specialty. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1197-1205